PENGARUH PENGAJARAN APLIKASI WHATSAPP TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SD - Muhardila Fauziah; Tatat Hartati; vismaia S Damaianti; Yeni Sulaeman (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
Early in 2020, Pandemic Covid-19 spread in almost all regions of Indonesia which resulted in changing in the teaching process. Teaching was carried out by using various digital applications, one of which was WhatsApp application. The purpose of this study was to describe the teaching through WhatsApp application as a learning resource and tool, and to find out the effect of WhatsApp on the students’ reading ability at grade 1. The method in this study was a quantitative experimental research with a questionnaire, interviews, and observations as the instruments. The subjects of this study were grade I students who were registered in elementary schools and participating in teaching with WhatsApp. The results of the study illustrated that WhatsApp application used by the teacher was ineffective as a medium and learning tool for grade 1 elementary school students. The data revealed that 70% of parents stated that their children were not yet able to read, 12% of parents stated that their children were not able to recognize and pronounce words correctly. In conclusion, WhatsApp had no effect on students' initial reading abilitys during the Covid-19 pandemic as the result of the hypothesis testing indicated that the probability value (significance) was 0.000; thus, Ho was rejected. Using WhatsApp application as a medium for early reading was not recommended.